IMPLEMENTASI PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN IPS (Studi Kelas IV SDN Tamansari 4 Probolinggo) - Wardana, Ludfi Arya; Husen, Choirun (JURNAL PENDIDIKAN DASAR NUSANTARA, 2017)
This research aim is to improve student achievement in the fourth grade social studies SDN Tamansari 4 Probolinggo City by using a scientific approach consisting of observing, asking, trying, reasoning and communicating. The method of this research is classroom action research (CAR) conducted collaboratively between researchers and teachers. The subjects consisted of 30 students with heterogeneous ability. The study was conducted for two cycles, each cycle consisting of two learning meetings. Technique of collecting data is done through observation, interview, documentation and also student achievement test. The results showed there was an increase, both seen from the aspect of participation in opinion, cooperation and complete the task. The result of the students test known in first cycle obtained the average of the class is 71 with the complete student of 22 students or 73,33%. In second cycle, the average class is 77,14 with the complete student of 25 students or 83% (learning mastery criteria ≥ 70). From the data can be interpreted that the application of scientific approach can improve student achievement in the subjects of social studies grade four SDN Tamansari 4 Probolinggo City. Keywords: scientific approach, learning achievement, classroom action research